James A. Lee. The environment, public health and human ecology. Baltimore : World Bank, 1985. 288 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1987)
JAMES A. LEE. The environment, public health and human ecology, World Bank, Baltimore, 1985.